2011
DOI: 10.1016/j.immuni.2010.12.018
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I RNA Helicase Activation of IRF3 Transcription Factor Is Negatively Regulated by Caspase-8-Mediated Cleavage of the RIP1 Protein

Abstract: Excessive responses to pattern-recognition receptors are prevented by regulatory mechanisms that affect the amounts and activities of the downstream signaling proteins. We report that activation of the transcription factor IRF3 by the ribonucleic acid sensor RIG-I was restricted by caspase-8-mediated cleavage of the RIP1 protein, which resulted in conversion of RIP1 from a signaling enhancer to a signaling inhibitor. The proteins RIP1 and caspase-8 were recruited to the RIG-I complex after viral infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 32 publications
(48 reference statements)
5
174
0
Order By: Relevance
“…2 B and C). A mutually nonexclusive possibility is that the absence of Nt-arginylation in ATE1-deficient mice not only augments the RIPK1/caspase-8 positive feedback but also increases, through a mechanism to be understood, the TNFα-induced processive degradation of fulllength RIPK1, a conditionally short-lived protein (6,33,36). In contrast to results with ATE1-deficient mouse tissues (Fig.…”
Section: Partial Ablations Of the Arg/n-end Rule Pathway Make Cellsmentioning
confidence: 85%
“…2 B and C). A mutually nonexclusive possibility is that the absence of Nt-arginylation in ATE1-deficient mice not only augments the RIPK1/caspase-8 positive feedback but also increases, through a mechanism to be understood, the TNFα-induced processive degradation of fulllength RIPK1, a conditionally short-lived protein (6,33,36). In contrast to results with ATE1-deficient mouse tissues (Fig.…”
Section: Partial Ablations Of the Arg/n-end Rule Pathway Make Cellsmentioning
confidence: 85%
“…A recent study has shown RIP1 to be recruited to the RIG-1 mitochondrial complex with ubiquitination of RIP1 serving to provide docking sites for key signalling molecules such as the IKK complex that activates NFkB. 120 However, RIP1 can also facilitate recruitment of caspase 8 to the complex, resulting in the cleavage of RIP1 and the generation of an inhibitory RIP1 fragment that represses RIG-I-induced activation of IRF3. Thus RIP1 is a key regulator of the temporal expression of virus-responsive genes.…”
Section: Rip Kinases and Nucleic Acid Sensingmentioning
confidence: 99%
“…23,24 Therefore, we investigated whether RIP-1 was involved in the death of c-FLIP L -deficient T lymphocytes. Autophagy is enhanced in c-FLIP L À / À T lymphocytes.…”
Section: Cellular Caspase 8 (Flice)-like Inhibitory Protein (C-flip) mentioning
confidence: 99%
“…24 Studies in human fibroblast cell lines showed that caspase 8 mediated the cleavage of RIP-1 to produce an inhibitory RIP-1 fragment. 23 It is possible that a similar inhibitory mechanism may occur in T lymphocytes: c-FLIP L may regulate RIP-1 activity by recruiting RIP-1 to the DISC for caspase 8-dependent degradation. In this model, without c-FLIP L , the recruitment of RIP-1 is blocked.…”
Section: Necroptosis In C-flip L -Deficient T Cells Involves Reactivementioning
confidence: 99%